(untitled) (Journal of Educational Sciences, 2016)
Expertise is an examination of some issue and its resolution with the help of specialists. Questions of scientific expertise of research results are relevant in the present. Purpose of the article is developing practical expert recommendations to improve the quality of scientific research activity. The article presents the classification of types of expertise. The traditional criteria for assessing the quality of research – the relevance, novelty, theoretical and practical importance – are considered. In the modern age, these criteria are supplemented by the requirement of materials uniqueness, the presentation of results in foreign databases and others. Laws of growth, dispersion and aging of information are revealed. On its basis recommendations are offered for the carrying out research of sources of scientific and technical information. The search for ways to perfect the criteria for evaluating scientific research continues. This will promote the development of the quality of scientific research.